Student Satisfaction Level in Individual Counseling Services at MAN 13 Jakarta - Mahendra, Damar Putra; Asni , Asni (CV. Publikasi Indonesia, 2024)
This research aims to determine student satisfaction with individual counseling services at MAN 13 Jakarta. The research method used in this study is quantitative descriptive. The sampling technique used is purposive sampling. The instrument provided is an instrument to measure satisfaction based on service quality (SERVQUAL). The validity test contained 38 valid statements and 17 invalid statements out of 55 statements. The reliability test result obtained a result of 0.953, so the reliability value of this instrument is very high and reliable. The overall research results are 77% in the reasonably satisfied classification, 16% in the satisfied category, and 7% in the dissatisfied classification. Furthermore, based on dimensions, it is known that the dimension of physical evidence gets the most significant percentage, 82%. The reliability dimension is second, with a rate of 79%. In addition, as many as 78% were for the responsiveness dimension, followed by two other dimensions with the same percentage, namely 74% for the certainty and empathy dimensions. This shows the need for evaluation by BK teachers so that the services provided to students can be provided effectively and well so that students' satisfaction with individual counseling services will be high.